SMAD2/SMAD3 como eje regulador en la patogénesis del cáncer de endometrio y la respuesta a la terapia hormonal - Reyna-Villasmil, Eduardo (2025)
Endometrial cancer stands out as the most common gynecological tumor inindustrialized nations. It's crucial to thoroughly understand its molecular processes, particularly in hormone-dependent cases that often exhibit treatment resistance.Research attention has focused on SMAD2/SMAD3, crucial proteins in thetransforming growth factor beta signaling pathway. These proteins are fundamental for cellular development and proper functioning, encompassing proliferation and differentiation. However, their role in cancer is ambivalent: they act as tumorinhibitors in the early stages and promote invasion and metastasis in later stages.Various studies reveal that SMAD2/SMAD3 are essential for endometrial stability, and their alteration directly contributes to tumor progression. Furthermore, they interactwith estrogen and progesterone, altering the response to hormonal therapies. Thisinteraction is vital for creating new therapeutic targets and predictive biomarkers that improve the approach to endometrial cancer. The objective of this review is to analyze the role of SMAD2/SMAD3 as a regulatory axis in the pathogenesis and progressionof endometrial cancer, and their influence on responses to hormonal therapy, with the aim of identifying new therapeutic targets and predictive biomarkers.